Analisis Penentuan Harga Pokok Produksi Dan Harga Jual Produk Seragam Sekolah Pada UD. R. Cemerlang Singaraja - Ni Luh Sri Budi Lestari; Ni Wayan Yulianita Dewi (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
The study aimed at identifying the principal method for producing and selling the school uniform products in the UD. R. Cemerlang Singaraja. The study was designed using interactive model and qualitative data analysis techniques from Miles and Huberman. The subject and object of this research is the management of UD. R. Cemerlang Singaraja and methods of determining the cost of production and selling price. Data collection methods include interviews, observation and documentation. Research shows that factory overhead calculation and direct labor costs have not been detailed, in record-keeping and calculating not all the costs in detailed grouping, there is a discrepancy between the UD. R. Cemerlang Singaraja engineering and cost-based authors, according to the accounting theory of cost, due to the cost of machine reduction, PPN, rijek and discrepancies, the company has made a note of all charges issued in a simple way and has not applied the principal custom card usage. Keywords: Cost of Production, Selling Price, Factory Overhead Cost